Pengaruh Model Kooperatif Tipe Numbered Head Together (NHT) Terhadap Hasil Belajar Siswa Pada Tema 1 Subtema 2 di Kelas V Sekolah Dasar - Panso, Nurlathiifah; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
This study aims to determine the effect of the use of the NHT type of cooperative learning model on learning outcomes in learning theme 1 sub-theme 2 class V students of Public Elementary School in Cluster III Banuhampu Agam Regency. This type of research is a True Experimental Type Pretest - Post-test Control Group Design Sampling uses a random sampling technique with the results of several considerations obtained by the number of samples of 17 students in each class of Control and experimentation. The instruments used were in the form of tests. Data analysis techniques in this study used prerequisite tests in the form of normality and homogeneity tests and hypothesis testing using t-test results showed that Ha was accepted, that is, there was a significant effect in the use of the NHT type of cooperative learning model on learning outcomes theme 1 sub-theme 2 class V students of SD Negeri Se III group Banuhampu Agam Regency. This was evidenced from the results of t-test with significance level 5% obtained tcount 2,1235> t table 1,753. The learning outcomes obtained by the experimental group were higher than the control group, indicated by the average of the experimental group was 80,94 and the average control group was 70,58.